THE IMPACT OF TAX REFORM ON SMALL AND MEDIUM ENTERPRISES - Loso Judijanto; Anggriani Husain; Muhammad Syaiful (Adisam Publisher, 2025)
Tax reform is a broad area of regulatory change, technology implementation, and incentive policies. The research in this investigation uses the literature research method. The results show that the impact of tax reform on Small and Medium Enterprises is dualistic. On the one hand, reforms that prioritize transparency, simplicity, and are supported by clear guidelines are well received by Small and Medium Enterprises, as they ease the reporting process and improve tax compliance. On the other hand, complex and confusing reforms create uncertainty and operational challenges, especially for Small and Medium Enterprises that are less prepared in terms of technology and infrastructure. Therefore, technological readiness and supporting infrastructure play an important role in determining the effectiveness of tax reform. Furthermore, the need for support from the government, both in the form of tax incentives and education, greatly affects the success of Small and Medium Enterprises' adaptation to tax reform. Incentives such as tax subsidies or rebates help to reduce the financial burden, while training and education improve the understanding of Small and Medium Enterprises of the new rules. Thus, to achieve effective and equitable tax reform, a multifaceted approach is required involving improved regulations, increased access to technology, and ongoing support from the government.